Grundkurs Mobile Kommunikationssysteme : LTE-Advanced, UMTS, HSPA, GSM, GPRS, Wireless LAN und Bluetooth /: LTE-Advanced, UMTS, HSPA, GSM, GPRS, Wireless LAN und Bluetooth. (2015) - Sauter, Martin
No abstract available